Stabilization of Multicationic Redox Chemistry in Polyanionic Cathode by Increasing Entropy - Huangxu Li; Ming Xu; Huiwu Long; Jingqiang Zheng; Liuyun Zhang; Shihao Li; Chaohong Guan; Yanqing Lai; Zhian Zhang (Advanced Science, 2022)
Abstract Polyanionic compounds have large compositional flexibility, which creates a growing interest in exploring the property limits of electrode materials of rechargeable batteries. The realization of multisodium storage in the polyanionic electrodes can significantly improve capacity of the materials, but it often causes irreversible capacity loss and crystal phase evolution, especially under high‐voltage operation, which remain important challenges for their application. Herein, it is shown that the multisodium storage in the polyanionic cathode can be enhanced and stabilized by increasing the entropy of the polyanionic host structure. The obtained polyanionic Na3.4Fe0.4Mn0.4V0.4Cr0.4Ti0.4(PO4)3 cathode exhibits multicationic redox property to achieve high capacity with good reversibility under the high voltage of 4.5 V (vs Na/Na+). Exploring the underlying mechanism through operando characterizations, a stable trigonal phase with reduced volume change during the multisodium storage process is disclosed. Besides, the enhanced performance of the HE material also derives from the synergistic effect of the diverse TM species with suitable molarity. These results reveal the effectiveness of high‐entropy concept in expediting high‐performance polyanionic cathodes discovery.